Enhancing English Language Assessment through Adaptive Testing Systems: A Psychometric and Technological Approach - Rustamov Firdavs Rafael o‘g‘li; Jumayev Bekzodjon To‘ra o‘g‘li; Oripova Muhabbat Jo’raqulovna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
In recent years, adaptive testing has emerged as a transformative approach in English language assessment, combining psychometric rigor with digital innovation. Unlike conventional exams, adaptive systems adjust item difficulty dynamically according to the test-taker’s responses, providing precise, efficient, and personalized measurements. This paper examines adaptive testing from theoretical, technological, and pedagogical perspectives. It explores Item Response Theory (IRT), item selection algorithms, automated scoring, and ethical considerations including fairness and accessibility. The study concludes that adaptive testing can enhance assessment reliability and learner engagement when designed responsibly, offering promising directions for both high-stakes examinations and classroom evaluations.